The Relationship Between Country Branding Components and Competitive Advantage - Yapraklı, Tevfik Şükrü; Absalan, Ali; Ünalan, Musa (My University, 2020)
The goal of the current research work is examining the association between competitive advantage and country branding in view of citizens. Country branding is the core of managing which plays a vital role in managing the sustainable competitiveness of a nation. Country competitiveness is a concept which shows the degree to which a country can be differentiated from its rivals in the field of global competition. Data collected from Erzurum in Turkey and Urmia in Iran. Convenience sampling method was used in this study. Having determined the validity of data through excluding the missing inputs, 604 subjects were obtained to in order to conduct the considered analysis. Participants of the study involved 286 and 318 individuals from Turkey and Iran countries, respectively. Turkish citizens exhibited higher levels of emotional, physical, financial and social appeal than Iranian citizens. In addition, there was a significant positive correlation between physical, financial and leadership components and competitive advantage in both countries.
Keywords: Siyasi Bilimler; İşletme; Sosyoloji; İktisat